2016
DOI: 10.1007/s11746-016-2894-6
|View full text |Cite
|
Sign up to set email alerts
|

Production and Emulsifying Effect of Polyglycerol and Fatty Acid Esters with Varying Degrees of Esterification

Abstract: emulsions, depending on the length of the acid hydrocarbon radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Analysis of the emulsifying ability of esters 6b‐d showed that unlike PGL esters previously studied by us (Shikhlaliev et al, ), the degree of polyglycerin esterification did not significantly affect the emulsifying effect. This is probably due to the presence in the structure of the products of 6b‐d compounds D, P, Q , similar to PGPR.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…Analysis of the emulsifying ability of esters 6b‐d showed that unlike PGL esters previously studied by us (Shikhlaliev et al, ), the degree of polyglycerin esterification did not significantly affect the emulsifying effect. This is probably due to the presence in the structure of the products of 6b‐d compounds D, P, Q , similar to PGPR.…”
Section: Resultsmentioning
confidence: 60%
“…These conditions were chosen as model in the study of the interaction of epoxidized triacylglycerols and methyl esters of unsaturated fatty acids with glycerol and PGL. Earlier, we have obtained esters of fatty acids and PGL using this method (Shikhlaliev et al, ). On the one hand, glycerol can polymerize into PGL under these conditions, and, thus, the number of stages is reduced.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations